Komik Strip Sebagai Media Kritik Sosial: Studi Pada Akun Instagram @Komikin_Ajah - Nuritia Ramadhani; Riza Darma Putra (Fakultas Ilmu Komunikasi Universitas Pancasila, 2017)
Comics in general have been present in the print media such as newspapers, but the availability is only considered as a mere entertainment medium and is not considered as a media delivery message. Currently comics have been present through social media and used as a medium for delivering messages, wrongly in the form of criticism. Creators use comic media as a means of delivering the message, with that background then this study aims for comic strips as a medium of social criticism. The results showed that creators use comics as a medium of delivery of messages in the form of social criticism, by doing various considerations before using. In addition, the comics themselves are used by creators to perform social movements such as the #MasihMelawanAsap and #BerbagiHarapan movements.